Communication Behavior Based on Gender Reponsive in Primary School - Ernita Arif; Aida Vitayala S Hubeis; Basita Ginting Sugihen; Ninuk Purnaningsih; Amiruddin Saleh (Jurnal Komunikasi Pembangunan, 2014)
In addition to poor communication, the teacher is still  differentiate between male and female students. If the  communication behavior of the teacher in the learning process is not gender responsive, it will affect the successful of the learning process. Gender responsive teacher communication behavior will improve the quality of learning. The objective of this research were to analyze the communication behavior of male and female teacher in urban and rural areas. The research was conducted in the city of Padang and Padang Pariaman District began in August to December 2013. Total sample of 200 people consisting of 100 male and 100 female  were scattered in cities and in villages.Data analysis using  Spearman rank,  Chi Sguare correlation. The research results showed that verbal communication  behaviors that include snarl words, purr words, degrading words, confirmation, taboos and euphemisms including the high category is spoken by male and female the teacher in both  urban and rural, communication behavior nonverbal such as tone of voice, facial expression, eye contact, proximity, and the average time high.Keywords: teacher, communication behavior, verbal and nonverbal, gender responsive